EFEKTIVITAS PELAKSANAAN PENERTIBAN PROSTITUSI DI KOTA PEKANBARU - Sharon Nitami Marreta; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Among the many social problems that occur in Indonesian society is the activity of prostitution. The problem of prostitution is a complicated matter, many things are related there, therefore this issue really needs special attention from the government. Dikota Pekanbaru prostitution problem has existed since a long time, since there are many places of entertainment, be it cafe-cafe, dim store, massage parlor and some are hung on the sidewalks or shops that are considered safe to conduct transactions Their sex. Efforts of Pekanbaru municipal government and security apparatus and related institutions in dealing with the practice of prostitution is continuously conducted in efforts to suppress and overcome the number of women who work as commercial sex workers in the city of Pekanbaru. This study aims to determine the effectiveness of Procedure Control Procedures in Pekanbaru City. The theory used in this study is the theory according to Gibson about measuring the effectiveness of an activity. Informant in this research is Satuan Polisi Pamong Praja Pekanbaru. The research method used is qualitative research. In the data collection, the researcher uses interview, observation, and documentation techniques based on Snowball Sampling. The results of this study indicate that the effectiveness of the implementation of prostitution control in the city of Pekanbaru has not been implemented properly and optimally. In other words there are still many problems that arise in the implementation. Such as lack of facilities, careful planning, special programs are not written, and supervision system. This causes the control does not go as expected. The factors that influence the implementation of prostitution control are, among others, lack of human resources, budget, facilities, and community participation. It has a very important influence on the effectiveness of the implementation of prostitution control in the city of Pekanbaru.Keywords: Effectiveness, Implementation, Control